Role of arginine vasopressin and angiotensin II in cardiovascular responses to combined acute hypoxemia and hypercapnic acidosis in conscious dogs. - Rose, C E (1984)
The physiological relationship of increased circulating angiotensin II and vasopressin to circulatory changes during combined hypoxemia and hypercapnic acidosis is unclear. To evaluate the role(s) of angiotensin II and vasopressin, seven unanesthetized female mongrel dogs with controlled sodium intake (80 meq/24 h X 4 d) were studied during 40 min of combined acute hypoxemia and hypercapnic acidosis (PaO2, 36 +/- 1 mmHg; PaCO2, 55 +/- 2 mmHg; pH = 7.16 +/- 0.04) under the following conditions: (a) intact state with infusion of vehicles alone; (b) beta-adrenergic blockade with infusion of d,l-propranolol (1.0 mg/kg bolus, 0.5 mg/kg per h); of the vasopressin pressor antagonist d-(CH2)5Tyr(methyl)arginine-vasopressin (10 micrograms/kg); and (d) simultaneous vasopressin pressor and angiotensin II inhibition with the additional infusion of 1-sarcosine, 8-alanine angiotensin II (2.0 micrograms/kg per min). The rise in mean arterial pressure during the combined blood-gas derangement with vehicles appeared to be related to increased cardiac output, since total peripheral resistance fell. Beta-adrenergic blockade abolished the fall in total peripheral resistance and diminished the rise in cardiac output during combined hypoxemia and hypercapnic acidosis, but the systemic pressor response was unchanged. In addition, the rise in mean arterial pressure during the combined blood-gas derangement was unaltered with vasopressin pressor antagonism alone. In contrast, the simultaneous administration of the vasopressin pressor and angiotensin II inhibitors during combined hypoxemia and hypercapnic acidosis resulted in the abrogation of the overall systemic pressor response despite increased cardiac output, owing to a more pronounced fall in total peripheral resistance. Circulating catecholamines were increased during the combined blood-gas derangement with vasopressin pressor and angiotensin II blockade, suggesting that the abolition of the systemic pressor response in the last 30 min of combined hypoxemia and hypercapnic acidosis was not related to diminished activity of the sympathetic nervous system. These studies show that vasopressin and angiotensin II are major contributors to the systemic pressor response during combined acute hypoxemia and hypercapnic acidosis.